2010
DOI: 10.1103/physrevb.82.054506
|View full text |Cite
|
Sign up to set email alerts
|

Large decrease in the critical temperature of superconductingLaFeAsO0.85compounds doped with 3% atomic weight of nonmagnetic Zn impurities

Abstract: We observed a large decrease in T c by no more than 3 at. % of Zn doped into the T c -optimized superconductor LaFeAsO 0.85 ͑T c =26 K͒, confirmed by measurements of electrical resistivity, magnetic susceptibility, specific heat, Mössbauer spectroscopy, Hall coefficient, and an electron probe microanalysis. The rate ϳ9 K/ % is remarkably higher than others achieved by nonmagnetic impurities. The T c suppression is likely due to pair breaking caused by scattering associated with the highly localized electronic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 56 publications
5
56
0
Order By: Relevance
“…The behaviors of T c suppression by impurity doping in both RFeAs(O,F) and LaFeP(O,F) are very similar, i.e., the magnetic impurity of Mn strongly reduces T c , while the nonmagnetic impurities do not largely destabilize the SC state [29][30][31][32]. The previous and present experimental results may have indicated that these effects of destabilization of superconductivity by magnetic and nonmagnetic impurities are a common feature in iron-based SC materials.…”
Section: Discussionsupporting
confidence: 62%
“…The behaviors of T c suppression by impurity doping in both RFeAs(O,F) and LaFeP(O,F) are very similar, i.e., the magnetic impurity of Mn strongly reduces T c , while the nonmagnetic impurities do not largely destabilize the SC state [29][30][31][32]. The previous and present experimental results may have indicated that these effects of destabilization of superconductivity by magnetic and nonmagnetic impurities are a common feature in iron-based SC materials.…”
Section: Discussionsupporting
confidence: 62%
“…In The anisotropic lattice feature is remarkably contrast with what was found for LaFeAsO 1-δ [26] and TbFeAsO 1-δ [27], in which the unit cell is isotropically contracted with increasing amount of the oxygen vacancies. Nevertheless, the systematic lattice change is indicative of successful doping of the oxygen vacancies into the structure, although we were unable to measure the net oxygen concentration by a chemical method because of the toxic effects.…”
Section: Results and Discusionmentioning
confidence: 62%
“…We thus focused on a specific Fe-based compound that has increasing distance between the layers, as was successful in the oxyarsenides such as LaFeAsO 1-δ [26] and TbFeAsO 1-δ [27].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the metal-insulator transition on T c is also known for Cu oxides. [22][23][24] Rather strong T c -suppression observed for Zn doped samples prepared under high pressure 25) can also be understood by this effect. In this case, to remove the effects of grain boundaries, we use a factor 1/2 smaller than the value 1/4 used above, considering the high pressure preparation of the samples and easily find that the critical resistivity for zero T c roughly corresponds to the sheet resistance of 6.45 k .…”
Section: -11)mentioning
confidence: 87%